FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN OBAT TRADISIONAL DAN OBAT SINTETIK PADA MASYARAKAT DESA TINCO KECAMATAN CITTA KABUPATEN SOPPENG - Suprapto Prayitno; Andi Armisman Edi Paturusi; Lisna Puspitasari (Akademi Farmasi Yamasi Makassar, 2026)
The selection of medicine types is a crucial part of community health behavior. This study aims to identify the factors influencing the purchasing decisions of traditional and synthetic medicines in Tinco Village, Citta District, Soppeng Regency. The research method used was descriptive qualitative involving 100 respondents selected through purposive sampling technique. Data collection was carried out using open-ended questionnaires which were then coded and analyzed descriptively. The results showed that the community tended to use medicines situationally based on the type and severity of the disease. Factor analysis showed that psychological factors dominated purchasing decisions (82%), followed by personal factors (78%), cultural factors (74%), and social factors (68%). Previous usage experience and drug availability were the main determinants. It is concluded that medicine purchasing decisions in the Tinco Village community are adaptive and significantly influenced by perceptions of effectiveness as well as individual internal and external factors.